The children of Ambodirafia go to school whenever they want (Journal of Parents and Teachers, 2026)
In this section, you will find ideas, experiences and examples that may be helpful in class or at home. You will learn about the unique reality of children in a small village in Madagascar, who go to school when they want to, when there is nothing to do at home. Also of interest are the “taste classes” developed by the French Ministry of Education and Culture, which ultimately encourage pupils to eat everything. In addition, there is a short article about the life of the Amish Mennonites, where to find educational software, and the farewell to Pope John Paul II by two hundred young Spaniards in Santo Domingo.
Keywords: school, adaptation, taste and smell, Mennonites, John Paul II